A Methodology to Teach Life-Skills in Connection to Sport Practice - Goudas Μάριος (Inquiries in Physical Education and Sport, 2022)
This paper describes a life-skills program for young athletes and physical education students that is taught in the sport-field in connection to sport practice. Life-skills taught in the program include goal-setting, goal planning, positive thinking, self-talk and problem-solving. The program requires minimal time investment by athletes and coaches and its implementation is not at the expense of sport-skills training. Rather, results from studies that evaluated the program showed that it facilitates the enhancement of sport performance. The related publications have provided only a brief description of the program. Therefore, the current paper outlines the program in more detail to facilitate those interested to implement it.